The Effect of Professional Allowances and Teacher Professionalism on Teacher Performance - Farezhena, Swastika; Wijayaningsih, Lanny (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose – The welfare of teachers as educators must be considered, for example, by providing professional allowances on time, because if they are late, it will hamper teachers' performance. In addition, teacher performance is deficient due to the lack of workshops and the assumption that the teaching profession is only limited to earning income. Therefore, this study aims to determine the effect of professional allowances and teacher professionalism on teachers at the level of early childhood education.Design/methods/approach – This study uses explanatory research with a quantitative approach. Sampling in this study uses a saturated sample technique, which means that all populations are used as respondents. The data collection method used a questionnaire with a Likert scale. The questionnaires were distributed to all early childhood education teachers in Bergas District, Semarang Regency, who received professional allowances to be filled out by respondents. The data that has been collected is then analyzed using multiple linear regression analysis.Findings – The results of the t-test show that the regression coefficient of the professional allowance variable is 0.621, with a significance of 0.001. it means that partially the professional allowance has a positive effect on teacher performance. Then, the variable of teacher professionalism has a regression coefficient of 0.795 with a significance value of 0.000 which means that partially teacher professionalism has a positive effect on teacher performance. Meanwhile, the results of the F-test show that the F value is 20,130 and is significant at 0.000. It means that professional allowances and teacher professionalism can simultaneously affect teacher performance.Research implications/limitations – This research is limited to two independent variables, and the research location is only in one area. Future research is expected to explore more deeply the factors that can affect the performance of Early Childhood Education Programs teachers with a broader research location. Practical implications – This research is expected to provide input to early childhood education teachers, school institutions, and education offices related to teacher performance, especially in Bergas District, Semarang Regency. The implication that needs to be applied to keep teacher performance high and optimal is to pay attention to the professional allowances given to teachers and teacher professionalism.Originality/value – This study adds teacher professionalism as one of the factors that can affect teacher performance. This research also makes Early Childhood Education Programs teachers research respondents. Paper type Research paper